Lidar measurements of stratospheric aerosols enhanced after the eruption of Mt. Pinatubo: Alaska, winter 1991/1992 - Iwasaka, Yasu-nobu; Fujiwara, Motoo; Matsunaga, Katsuji; Nagatani, Masahiro; Nakada, Hiroshi; Akiyoshi, Hideharu; Yasumatu, Satoshi; Mori, Ikuko; Kondoh, Kouji; Nakane, Hideaki (National Institute of Polar Research, 1993)
P(論文) Lidar measurements made at Poker Flat, Alaska in winter 1991/1992 suggest that stratospheric aerosols were extremely enhanced after the volcanic eruption of Pinatubo. The vertical profile of aerosol concentration had maxima 16-17km, and 22-23km. An additional aerosol layer was identified only in the measurements of December 15,1991. departmental bulletin paper